Auditory Hallucinations as a Rare Presentation of Occipital Infarcts - Firas Ido; Reina Badran; Brandon Dmytruk; Zain Kulairi (Case Reports in Neurological Medicine)
A stroke is a clinical syndrome characterized by a focal neurologic deficit that can be attributed to a vascular territory within the brain. The presenting features of an acute stroke depends on the area of the brain affected. Although unusual, the presenting feature may include psychosis with auditory and/or visual hallucinations. A 56-year-old female was admitted to the psychiatric unit after threatening her husband with a knife. She reported experiencing altered sensorium for one week with suicidal and homicidal command hallucinations. Given the acute onset, brain images were obtained to rule out an organic etiology. A brain MRI revealed an acute right occipital lobe infarct with hemorrhagic transformation. The patient’s symptoms were self-limited, resolving without antipsychotic medications. Psychosis with auditory hallucinations is not commonly reported following stroke. Since histologic and functional alterations in the occipital lobe appear to play a significant role in psychosis of schizophrenics, it is likely that ischemia in the same area may cause similar changes. Familiarity with this rare presentation is important, as it prevents a delay in diagnosis, which may negatively impact the outcome.